Choroidal Coloboma in a Case of Tay-Sachs Disease. (10th September 2014) - Ahmed, Nasreen Raees; Tripathy, Koushik; Kumar, Vivek; Gogia, Varun
Abstract : Coloboma as an ocular finding has been documented in various syndromes. Here we have a case of infantile Tay-Sachs disease associated with unilateral choroidal coloboma. To the best of our knowledge, such an association has not been documented in the literature. Whether such an association is a matter of chance or signifies the involvement of ganglioside metabolism in ocular embryogenesis remains to be elucidated.